Tratamento termomecânico e seus efeitos nas propriedades da Simarouba amara (Aubl.) - Freitas, Ana Salgado (2016)
The pressure concentrated in a small group of tropical species necessitates greater investment in research and breeding techniques in lesser known species in an attempt directs them to multiple uses. This work aims to evaluate the influence of thermomechanical treatment on colorimetric properties and modulus of elasticity of timber marupá, in order to use it on the floor segment. The results showed a significant change with temperature effect on the color and the property of elasticity of wood. In general, an improvement in dynamic elastic modulus as the speed varied with each treatment shown, having lower values for the treatments with high pressure. The dark wood (lower L * values and higher values of a *) with application of temperature. The colors of wood marupá after treatments, combined with property of elasticity enhances this species as an option for the flooring industry.